3D imaging using narrowband bistatic MIMO radar. Issue 15 (1st July 2014) - Yang, Jianchao; Su, Weimin; Gu, Hong
Abstract : A new method for three‐dimensional (3D) imaging via a narrowband bistatic multiple‐input–multiple‐output (MIMO) radar with two uniform rectangular arrays is presented. After matched filtering and phase compensation, the method utilises the 2D cross‐range images measured by the transmit and receive arrays to reconstruct the 3D image of the target. Compared with the 3D wideband monostatic MIMO imaging, lower hardware cost can be achieved since the narrowband waveforms are employed. In addition, the range alignment in wideband imaging can be avoided for the poor range resolution of the narrowband waveforms.